Black American Literature and Humanism - Miller, R. Baxter (Book collections on Project MUSE., 2015)
For Black writers, what is tradition? What does it mean to them that Western humanism has excluded Black culture? Seven noted Black writers and critics take up these and other questions in this collection of original essays, attempting to redefine humanism from a Black perspective, to free it from ethnocentrism, and to enlarge its cultural base. Contributors: Richard K. Barksdale, Alice Childress, Chester J. Fontenot, Michael S. Harper, Trudier Harris, George E. Kent, R. Baxter Miller.